Transnational campaigns for the Amazon: NGO strategies, trade and official responses - Zhouri,Andréa (2000)
The campaign against the illegal mahogany trade from the Amazon has increased the need for special working links between NGOs based in Brazil and those located in the Northern hemisphere, particularly Britain, since the UK is regarded as one of the major importers of that particular timber. The article discusses the origins, development and different strategies of the mahogany campaign -the major transnational campaign for the Amazon rainforest in the 1990s- as well as the reactions from the timber trade and the Brazilian government. Considering the interface of social justice and forest issues, the analysis presents the ways in which the Amazon is understood and projected into the global sphere, and how such a global perspective -currently dominated by efforts towards timber certification through the Forest Stewardship Council (FSC)- may render a more complex local reality invisible.